Effects of acidic functional groups on dielectric properties of sodium alginates and carrageenans in water. (22nd January 2015) - Tsubaki, Shuntaro; Hiraoka, Masanori; Hadano, Shingo; Okamura, Kei; Ueda, Tadaharu; Nishimura, Hiroshi; Kashimura, Keiichiro; Mitani, Tomohiko
Highlights: Acidic functional groups and counter ions of hydrocolloids induced conduction loss. Conductivity determined the dielectric property of the water-hydrocolloid system. Dynamics of water molecule and H + also affected the dielectric property. Abstract: This study investigated the dielectric properties of sodium alginates and carrageenans in water at frequencies between 100 MHz and 20 GHz in regard to water-hydrocolloid interactions via acidic functional groups. Both sodium alginates and carrageenans showed conduction loss at lower frequencies and dielectric loss at higher frequencies. Reduction and desulfation of sodium alginates and carrageenans, which decreased the numbers of acidic functional groups, decreased their conduction loss. In addition, H + -form carrageenans showed the highest ionic conduction. Correlational analysis of dielectric properties and related physical parameters showed that the loss tangent (tan δ ) of the hydrocolloid solution was determined by the conductivity of the aqueous solution. Especially at pH below 2, strong H + conduction was associated with high tan δ probably due to the Grotthuss mechanism. The molecular dynamics of free water and H +, viscosity conditions were also suggested to be associated with dielectric property of water-hydrocolloid system.